Selecting for useful properties of plants and fungi – Novel approaches, opportunities, and challenges - Kersey, Paul J.; Collemare, Jerome; Cockel, Christopher P.; Das, Dibakar; Dulloo, Mohammad Ehsan; Kelly, Laura J.; Lettice, Eoin; Malécot, Valery; Maxted, Nigel; Metheringham, Carey; Thormann, Imke; Leitch, Ilia J. (Wiley, 2020)
Humans use plants and fungi for a wide range of purposes and, over millennia, have improved wild species by selecting for and combining genetic variation. Improvements in DNA sequencing technologies have enhanced our capacity to identify and manipulate genetic diversity, increasing the range of variation that can be utilized, and accelerating the breeding cycle to reduce the time taken to develop and put new varieties to use. Most recently, the CRISPR/Cas9 gene editing technology has greatly increased our capacity to directly introduce novel genetic variants without unwanted associated material. Moreover, increased knowledge of metabolic pathways resulting from genomic analysis can be used to design new varieties with desired properties with increased precision. Selecting for, or engineering, desirable variants has increased the usefulness of plants and fungi to humans, but at the cost of reducing their genetic diversity, decreasing their resilience and reducing the stock of variation available for future use. Conservation of genetic biodiversity is thus an essential counterpart of crop improvement and is essential to ensure that crop species retain resilience to emerging threats. Conservation efforts are focused on orphan crops, wild relatives of crop species, and landraces; in and exsitu efforts are complementary. Informatic approaches can inform use of these materials in breeding programmes even in the absence of genomic information. The application of some of these approaches may be restricted by ethical, legal, or organizational obstacles. If these can be overcome, there is great potential to unlock previously untapped reservoirs of biodiversity for human benefit.